Capsaicin on stem cell proliferation and fate determination: a novel perspective - Yuan, Mengmeng; Zhao, Lucy; Li, Yuhong; Gao, Xiumei; Zhang, Boli; Zhang, Deqin; Li, Yue (Pharmacological research, 2021)
Capsaicin (CAP), a member of the vanilloid family, is the main active component of chili peppers, which has been widely explored for its various pharmacological effects and influence on cell physiology, such as axonal growth and apoptosis of tumor cells. In particular, CAP plays a crucial role in determining the proliferation and fate specification of stem cells by modulating a variety of signaling pathways, such as PPARγ, C/EBPα and Notch signaling. Since CAP-mediated processes are complex and multifactorial, we hope to achieve a better understanding of these processes and their implications in clinical applications. This review aims to shed light on the influences and mechanisms of CAP on the actions of various stem cells in adults and discusses the role of CAP in the different process of stem cell behaviors, including proliferation and differentiation. Our purpose is to provide certain prospects for the application of CAP and stem cell therapy in treating diseases.
Gesehen am 03.03.2022